2001
DOI: 10.1029/2001gl013860
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the latitude dependence of the location of the martian magnetic pileup boundary

Abstract: [1] We report observations that show the dependence of the altitude of the magnetic pileup boundary (MPB) at Mars on planetary latitude. As seen by the Mars Global Surveyor Magnetometer/Electron Reflectometer instrument, the MPB is further away from Mars on average at southern latitudes than at northern latitudes. The data are consistent with a MPB distance mapped to the terminator plane that does not vary with latitude in the northern hemisphere, but increases with increasing southern latitude in the southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
80
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 11 publications
13
80
0
Order By: Relevance
“…It is worth noting that the model of the MB position based both on MGS and Phobos-2 observations (Trotignon et al, 2006) gives a reasonable agreement with the above mentioned models. It is seen that the MB moves upward in the Southern Hemisphere (dashed curve) that is in the agreement with the MGS observations (Crider et al, 2002). At solar zenith angles SZA≥45 • the shift reaches ∼500 km.…”
Section: Access Of Solar Wind Electrons On the Daysidesupporting
confidence: 77%
See 1 more Smart Citation
“…It is worth noting that the model of the MB position based both on MGS and Phobos-2 observations (Trotignon et al, 2006) gives a reasonable agreement with the above mentioned models. It is seen that the MB moves upward in the Southern Hemisphere (dashed curve) that is in the agreement with the MGS observations (Crider et al, 2002). At solar zenith angles SZA≥45 • the shift reaches ∼500 km.…”
Section: Access Of Solar Wind Electrons On the Daysidesupporting
confidence: 77%
“…The boundary has been often refereed as the magnetic pileup boundary (Bertucci et al, 2003;Nagy et al, 2004). Crustal magnetic fields can contribute to the total pressure of the obstacle against the solar wind (Crider et al, 2002;Dubinin et al, 2006). Average positions of the bow shock (BS) and the magnetospheric boundary (MB) determined, respectively, from the MGS and MEX observations (Vignes et al, 2000;Dubinin et al, 2006) are also shown.…”
Section: Access Of Solar Wind Electrons On the Daysidementioning
confidence: 99%
“…Crider et al (2002) have found that the magnetospheric boundary moves upward with increasing southern latitude. Fraenz et al (2006) and Dubinin et al (2008a) have shown that the boundary above strong crustal sources can shift upward by ∼400 km as compared to the boundary in the northern hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…The crustal magnetic field will be included in a future study, with an improved spatial resolution of 150 km accompanied with a better description of the ionosphere. Note here that Crider et al (2002) and Dubinin et al (2006) 1 have reported a dependence of the MPB position on the presence of crustal fields.…”
Section: The Mpbmentioning
confidence: 95%